ANALYSIS OF THE USE OF DIGITAL WORKSHEETS IN PHYSICS EDUCATION IN THE LAST DECADE - Robi Saepudin; Asep Irvan Irvani; Resti Warliani (Relativitas: Jurnal Riset Inovasi Pembelajaran Fisika, 2026)
This study aims to analyze the use of digital worksheets in physics education over the past decade, using a bibliometric approach to examine publication trends, author contributions, and dominant keywords. The data collected includes 61 documents published between 2015 and 2025. The results show a sharp increase in publications in 2021, related to the response to the COVID-19 pandemic, followed by a significant decline in the subsequent years. Nevertheless, the use of digital worksheets has proven effective in enhancing students' understanding of complex physics concepts and supporting the development of critical thinking skills. In conclusion, although interest in this topic has increased, further research is needed to evaluate the long-term effectiveness and application of digital worksheets in hybrid or blended learning models to maximize the potential of technology in physics education.